Proceedings of the 3rd International Conference on Language, Literature, Culture, and Education (ICOLLITE 2019) 2020
DOI: 10.2991/assehr.k.200325.044
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Sokuon and Choon Used by Japanese Learners

Abstract: The research aimed to describe the errors and factors affecting errors made by learners in writing hiragana letters involving the elements of the word sokuon and choon. It also described the way to resolve errors made by the teacher and learners. This study was qualitative descriptive research, which was conducted in SMAN Rengat involving 20 Japanese language students of grade ten. The collected data were in the form of tests on choon and sokuon and interviews. It was ten questions for each session. The interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Research on double consonants (sokuon) in Japanese was also conducted by Wahyuni and Sutedi (2020) to determine the language errors and causal factors of Japanese language learners on the ability to read and write hiragana containing sokuon and choon. This study found that most of the errors in reading and writing words that contain double consonant sounds (sokuon) are because learners do not know the meaning of the word in question and do not know the actual rules of Japanese.…”
Section: □っきmentioning
confidence: 99%
“…Research on double consonants (sokuon) in Japanese was also conducted by Wahyuni and Sutedi (2020) to determine the language errors and causal factors of Japanese language learners on the ability to read and write hiragana containing sokuon and choon. This study found that most of the errors in reading and writing words that contain double consonant sounds (sokuon) are because learners do not know the meaning of the word in question and do not know the actual rules of Japanese.…”
Section: □っきmentioning
confidence: 99%
“…The research on the analysis of learner errors in learning Japanese as a second language has been conducted by numerous researchers, including those from Indonesia and other countries. These studies include analyzing errors in the use of particles (Inayah, 2020), the use of give-take verbs or "juju doushi" (Dewi, Saun & Putri, 2018;Ota, 2020), the use of the verbs ~iku, ~kuru (Fukunaga, Arinirahma, Rubenson, 2022), the chou-on (long vowel sound) and sokuon (double consonant) sounds (Wahyuni & Sutedi, 2020). However, there is a barely noticeable number that discusses the analysis of errors in the realization of Japanese language learners' speech acts.…”
Section: Introductionmentioning
confidence: 99%